2010
DOI: 10.1002/hup.1145
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind, placebo‐controlled pilot study of ondansetron for patients with obsessive‐compulsive disorder

Abstract: The results of this study show that ondansetron has positive effects on obsession and compulsion which start two weeks after the beginning of the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 20 publications
0
50
1
1
Order By: Relevance
“…The findings of small randomised placebocontrolled augmentation studies with 5-HT 3 antagonists provide evidence for the efficacy of the addition of ondansetron to fluoxetine [I (PCT)] (Soltani et al, 2010) and for the addition of granisetron to fluvoxamine [I (PCT)] (Askari et al, 2012). Three relatively small randomised placebo-controlled anticonvulsant augmentation studies indicate that the addition of topiramate to SSRIs reduces the severity of compulsions [I (PCT)] (Berlin et al, 2011), and of obsessive-compulsive symptoms [I (PCT)] (Mowla et al, 2010); and the addition of lamotrigine to SSRIs reduces the severity of obsessive-compulsive and affective symptoms [I (PCT)] (Bruno et al, 2012).…”
Section: Further Management After Nonresponse To Initial Treatmentmentioning
confidence: 99%
“…The findings of small randomised placebocontrolled augmentation studies with 5-HT 3 antagonists provide evidence for the efficacy of the addition of ondansetron to fluoxetine [I (PCT)] (Soltani et al, 2010) and for the addition of granisetron to fluvoxamine [I (PCT)] (Askari et al, 2012). Three relatively small randomised placebo-controlled anticonvulsant augmentation studies indicate that the addition of topiramate to SSRIs reduces the severity of compulsions [I (PCT)] (Berlin et al, 2011), and of obsessive-compulsive symptoms [I (PCT)] (Mowla et al, 2010); and the addition of lamotrigine to SSRIs reduces the severity of obsessive-compulsive and affective symptoms [I (PCT)] (Bruno et al, 2012).…”
Section: Further Management After Nonresponse To Initial Treatmentmentioning
confidence: 99%
“…The other strategy is augmenting an SSRI with a serotonin 5-HT 3 receptor antagonist [77]. One double-blind RCT has shown the benefits of augmenting an SSRI with granisetron in adult OCD [78], and two doubleblind RCTs have shown the benefits of ondansetron in adult OCD [79,80]. These treatments are clearly to be used by experts in true treatment-refractory OCD.…”
Section: Other Possible Medicationsmentioning
confidence: 99%
“…Augmentation of SSRIs with antipsychotic medication is the most evidence-based option, and a number of randomised double-blind placebo-controlled augmentation studies has shown that the addition of antipsychotic agents such as aripiprazole, haloperidol, olanzapine, quetiapine, or risperidone is effective in treatment-resistant OCD patients [18••]. The use of other medications such as ondansetron [19] and granisetron in combination with SSRIs [20] may also be effective. In addition, three relatively small randomised placebo-controlled anticonvulsant augmentation studies demonstrated that the addition of topiramate [21,22] or lamotrigine [23] to SSRIs reduced OCD severity.…”
Section: Ocdmentioning
confidence: 99%